Analisis Fungsi Laboratorium IPA, IPS, PPKn, Bahasa, dan Seni di Sekolah Dasar - Sarif Syahrudin; Junaidin (Mataram University, 2026)
The implementation of the Merdeka Curriculum in elementary schools encourages the use of a deep learning approach, which emphasizes students’ active participation in constructing knowledge through meaningful learning experiences. In this context, laboratories serve as one of the important learning facilities that support the achievement of such educational goals. This article aims to examine the various types of laboratories that can be utilized in elementary schools and to describe their functions and contributions to the implementation of deep learning. The study employed a library research method by reviewing relevant books, scientific articles, educational regulations, and other academic references. The collected data were analyzed descriptively to explain the role of each type of laboratory in the learning process. The findings reveal that elementary schools may utilize several types of laboratories, including science, social studies, civics, language, and arts laboratories. Each laboratory has its own specific function while complementing one another in fostering science process skills, critical thinking, social awareness, citizenship values, communication abilities, and creativity among students. Through laboratory-based activities, learners are provided with opportunities to gain direct, contextual, and meaningful experiences that enhance their understanding of concepts and support the goals of deep learning. Nevertheless, the effective implementation of laboratory activities remains constrained by several factors, including limited facilities, underutilization of available resources, and teachers’ capacity to manage laboratory-based learning. Therefore, greater efforts are needed to optimize the use of laboratories as an integral component of meaningful learning in elementary education.